2019
DOI: 10.32832/english.v13i1.3774
|View full text |Cite
|
Sign up to set email alerts
|

Dealing With Students’ Reticence in Speaking Activity in Efl Classroom

Abstract: Speaking is an activity in an English classroom in which students must integrate not only higher order thinking skills but also confidence. As a result, it can be problematic for students because they feel shy or reticent. This study aimed at finding out the cause of students’ reluctance in speaking activities. The study was framed by using classroom action research in which 2 cycles were employed. Each cycle consisted of four stages: planning, action, evaluation, and reflection. There were 40 students in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Recent studies on learner reticence have elaborated on student learning experiences and communicative behaviors in language classes (Zhang & Head, 2009;Liu & Jackson, 2011;Aghazadeh & Abedi, 2014;Nguyen, 2018;Aripin & Umam, 2019), where learners are ultimately expected to spend more time speaking especially using the language being learning. Speaking in the class activities and expressing ideas to strangers using the target language are the primary goals of students in these types of classes; however, research has revealed that reticence and anxiety are often present in these courses and may have a debilitating impact on language learning (Horwitz et al, 1986;Macintyre & Gardner, 1991;Liu & Jackson, 2008) that often manifest through speaking less to more negative forms of arousal (e.g.anxiety, tension, and incomprehensible speech).…”
Section: Learner Reticencementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on learner reticence have elaborated on student learning experiences and communicative behaviors in language classes (Zhang & Head, 2009;Liu & Jackson, 2011;Aghazadeh & Abedi, 2014;Nguyen, 2018;Aripin & Umam, 2019), where learners are ultimately expected to spend more time speaking especially using the language being learning. Speaking in the class activities and expressing ideas to strangers using the target language are the primary goals of students in these types of classes; however, research has revealed that reticence and anxiety are often present in these courses and may have a debilitating impact on language learning (Horwitz et al, 1986;Macintyre & Gardner, 1991;Liu & Jackson, 2008) that often manifest through speaking less to more negative forms of arousal (e.g.anxiety, tension, and incomprehensible speech).…”
Section: Learner Reticencementioning
confidence: 99%
“…Ten out of twelve (10 out of 12) participants reported that their learning environments at home affected their communicative behaviors in their online classes. Seven (7) out of these ten asserted that even though they have a dedicated desk or learning space at home -with some having a makeshift area due to the sudden shift to learning delivery-having to share a space with other family members deters them from communicating freely in their online classes. Participant 2C entered the university a few months into the onset of Covid-19 (during the first semester of the academic year 2020-2021), and their household's unpreparedness for having four people sharing the same space for work and school affected how she performed in her first few freshman classes.…”
Section: Factors That Contribute To Learner Reticencementioning
confidence: 99%
“…They worry about making mistakes or appearing unintelligent in front of their peers and teachers, leading them to retreat into silence. This lack of confidence is rooted in previous negative experiences, such as receiving criticism or feeling judged for their ideas or abilities (Aripin & Umam, 2019). Furthermore, students feel an overwhelming pressure to live up to certain expectations or standards set by themselves, their teachers, or their peers (Yu, 2016).…”
Section: Introductionmentioning
confidence: 99%